Development of two-phase interleaved synchronous rectification DC-DC for commercial vehicle engine ECU. (October 2019) - Mei, J W; Liu, J; Luo, T; Wei, H B
Abstract: The commercial vehicle diesel engine ECU and the electronically controlled common rail system power supply developed in this paper adopt the two-phase BUCK converter as the main loop. Considering the problems of large current fluctuation, high continuum diode loss and possible non-uniform current in parallel connection of traditional BUCK converter, a control strategy of two-phase staggered parallel synchronous rectifier BUCK converter is proposed. The relationship between current fluctuation and inductance, switching frequency and duty cycle of different operating modes is theoretically analyzed, and the current fluctuation of traditional BUCK converter is compared. The prototype test results show that the converter structure and control strategy effectively reduce the output current fluctuation and improve the system power density.